Geopora sinensis, a new truffle species from North China based on morphological and molecular data - Guo, Li-Jie; Xu, Yu-Yan; Fan, Li (Phytotaxa, 2019)
Geopora sinensis sp. nov. was described and illustrated from the soil under Picea wilsonii trees in North China based on molecular and morphological analyses in this paper. Morphologically G. sinensis is similar to G. cooperi, G. gilkeyae and G. tolucana, but distinguished from them by the combination of broadly ellipsoid ascospores and white hymenium. ITS-based phylogenetic analysis supports the establishment of the new species.